Identifikasi Jenazah Berdasarkan Hukum Islam Dan Hukum Humaniter Internasional - Siregar, Sawaluddin (Syekh Ali Hasan Ahmad Addary State Islamic University, 2025)
Challenges such as violent situations, armed conflicts, global pandemics, and natural disasters. The event found many unidentified graves. Is the opening of the body a legal obligation under Islamic law and International Humanitarian Law? or is it just a moral obligation to help worried family members? This study will provide an overview of the principles of Islamic law governing the burial of the body. Then compare it with the rules of International Humanitarian Law and show that both International Humanitarian and Islamic Law aim to end the suffering of the families of the missing. This study uses normative legal research. descriptive qualitative approach. Conclusion This article is the similarities and complementarities of the two legal bodies greatly contribute to being used by humanitarian workers to protect the families of the deceased and end the suffering of obtaining information about the fate and whereabouts of the body. Burial of unidentified bodies humanitarian workers must discuss with religious authorities. As well as the importance of storing burial information before burying it and participating in the development of forensic science in Islamic countries.